Bushen Huoxue Recipe Alleviates Implantation Loss in Mice by Enhancing Estrogen–Progesterone Signals and Promoting Decidual Angiogenesis Through FGF2 During Early Pregnancy - Ding, Jiahui; Tan, Xiujuan; Song, Kunkun; Ma, Wenwen; Xiao, Jing; Song, Yufan; Zhang, Mingmin (Frontiers in Pharmacology, 2018)
Bushen Huoxue Recipe (BSHXR) is a classic Chinese herbal prescription for nourishing the kidney and activating blood circulation. It consists of six herbs: Astragali radix, Angelicae sinensis radix, Ligustici Chuanxiong Rhizoma, Cuscutae semen, Taxilli Herba and Dipsaci Radix, and the main active constituents of BSHXR are Ferulic acid, Calycosin-7-Glucopyranoside, Hyperoside, Quercitrin and Asperosaponin VI. In clinical practice, BSHXR is traditionally used to treat failed pregnancy and its complications. However, little is known about the underlying mechanism of BSHXR for the treatment of implantation loss during early pregnancy. In the current study, controlled ovarian hyperstimulation was induced in mice as our implantation loss model, and we evaluated the effects of BSHXR on implantation, decidualization, decidual angiogenesis and reproductive outcome. We showed that BSHXR could regulate the supraphysiological levels of serum estrogen and progesterone observed in these mice, and also act on estrogen and progesterone receptors in the stroma and epithelium. BSHXR also enhanced FGF2 expression in the vascular sinus folding area of the decidua, thus potentially reducing implantation loss during early pregnancy and contributing to placentation and survival of the fetuses. Taken together, our findings provide scientific evidence for the application of BSHXR in the clinic as a treatment for implantation loss during early pregnancy, and warrant further investigation of BSHXR as an effective treatment for failed pregnancy and its complications.